THU0653 Changes in rheumatology provision and practice in a publicly-funded single payer healthcare system. (12th June 2018) - Widdifield, J.; Bernatsky, S.; Ahluwalia, V.; Barber, C.; Eder, L.; Hofstetter, C.; Kuriya, B.; Ling, V.; Lyddiatt, A.; Paterson, M.; Pope, J.; Thorne, C.
Abstract : Background: The global shortage of rheumatologists is an increasing concern. Statistics from physician surveys have projected changes in the workforce composition (ageing, feminization, and generational trends), which have implications for the workforce clinical activity. In order to adequately document the issues and potential solutions, more detailed information is needed regarding clinical activity, demographic changes and the implications of these, in a population-based sample. Objectives: To describe changes in the number, demographics and clinical activity of Ontario rheumatologists over the past decade. Methods: We analysed administrative health data from 2000 to 2013 in Ontario, Canada, where all 13 million residents are covered by a publicly funded healthcare system. Rheumatologists, and their characteristics, were identified using a validated physician registry. We used fee-for-service billing claims to quantify clinical activity levels expressed as full-time equivalents (FTE). Physicians below the 40th percentile of total billings were classified as providing less clinical activity (<1 FTE i.e. professor/scientist); 40–60th percentile were classified as 1 FTE; and >60 th percentile as >1 FTE (i.e. high volume community practice). Results: In 2000, there were 146 rheumatologists in Ontario (88 of whom worked ≥1 FTEs); this increased to 187 rheumatologists (114≥1 FTEs) in 2013. Despite the increase, due to an increase in the Ontario population over this time, the proportion of Ontarians seen by a rheumatologist annually remained constant (2.7%) as was the overall provincial per capita supply (1.2 rheumatologists per 75 000 population, 0.7 FTEs/75, 000). In 2000, 34% of rheumatologists were female compared to 48% in 2013. During this time, the proportion of rheumatologists aged >60 + years increased (16% to 26%). The annual median (IQR) number of days of clinical service decreased from 220 178–243 days in 2000 to 176 138–213 days in 2013. The percentage of rheumatologists with patient encounters on at least 209 days/year (an alternative FTE benchmark) showed a downward trend from 46% in 2000 to 22% in 2013. Male rheumatologists had more patient encounters each year, and a higher proportion of male rheumatologists worked as ≥1 FTE. Average practice sizes declined over time (figure 1A), as did the median number of patient encounters per rheumatologist per year (figure 1B). Conclusions: Although there has been an increase in the number of rheumatologists, the per capita supply and access to rheumatologists have remained unchanged. We observed changing workforce demographics and declining clinical activity over time. Factors affecting clinical activity (including an ageing and greater feminization of the workforce, clinic saturation, increasing care complexity, models of care, greater demands for continuing medical education and research activity) warrants further study. Disclosure of Interest: None declared